Whistleblowing : Recent Developments and Implementation Issues - World Bank (World Bank, Washington, DC, 2012)
These studies show that while whistle blowing is an important component of the corporate governance system of an organization, whistle blowers often face persecution. In this article reviews legislation that has been introduced to protect whistleblowers in a number of countries. The article also discusses the importance of the right corporate culture and attitudes towards whistle blowing, which are arguably just as important as legislation protecting whistle blowers. The article then discusses two real-life case studies on whistle blowing and concludes with key implementation issues which should be considered in developing a whistle blowing policy.